Malapposed, uncovered, underexpanded—intravascular imaging lessons on coronary stent thrombosis - Mankerious, Nader; Micha, Jonathon; Kufner, Sebastian (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Three decades after the first stent implantation in a coronary artery, contemporary percutaneous interventional techniques have reached very high levels of efficacy and safety. Successive iterations in stent design—from baremetal stents (BMS) to first and second-generation drugeluting stents (DES)—have seen a progressive decline in the rate of stent associated complications.